Acute Kidney Injury Induces Innate Immune Response and Neutrophil Activation in the Lung - Maeda, Akinori; Hayase, Naoki; Doi, Kent (Frontiers in Medicine, 2020)
Complication of acute kidney injury (AKI) is significantly associated with developing of acute respiratory failure (ARF), while ARF is one of the most important risk for AKI. These data suggest AKI and ARF may synergistically worsen the outcomes of critically ill patients and these organ injuries may not occur independently. Organ crosstalk between the kidney and the lung has been investigated by using animal models so far. This review will focus on innate immune response and neutrophil activation among the mechanisms that contribute to this organ crosstalk. AKI increased blood level of an inflammatory mediator high mobility group box 1, which induces innate immune reaction via toll-like receptor 4. Remarkable infiltration of neutrophils to the lung was observed in animal AKI models. IL-6 and IL-8 have been demonstrated to contribute to pulmonary neutrophil activation in AKI. In addition, the formation of neutrophil extracellular trap was also observed in the lung after exposure of renal ischemia reperfusion in animal model. Further investigation is necessary to determine whether targeting innate immune response and neutrophil activation will be useful for developing new therapeutics that improve multiple organ failure in critically ill patients.